Expansion of COS N Theta and SIN N Theta in terms of cosines and sines of multiple of theta by using noor's triangle - Muhammad, Noor (Malaysian Mathematical Society, 2013)
In the present study we introduced a triangle, like Pascal's triangle, to obtain directly the coefficients in the expansion of θ n cos and θ sin in terms of cosines and sines of multiple of θ , where n is any positive integer. This type of expansion is given by Datta et al. in which they have used the binomial theorem in order to obtain the coefficients therein. We name this triangle as "Noor's triangle".